ANALYSIS OF COMMUNITY-BASED ROAD MAINTENANCE TO OVERCOME CHANNEL EROSION IN RURAL AREAS - Nico Djundharto Djajasinga (Jurnal Kelola: Jurnal Ilmu Sosial, 2021)
This study aimed to analyze community-based road maintenance to overcome channel erosion in rural areas. This research uses descriptive qualitative research. The data used in this study were primary and secondary data; preliminary data was collected through in-depth interviews with the community and village heads through socialization activities regarding rural road maintenance techniques, while secondary data was collected through literature study to determine the condition of village facilities and infrastructure in Cianjur district, and data presentation using descriptive method. Based on the results of the research analysis, it can be concluded that in road maintenance, a Road Maintenance Acceleration Control Team has been formed as a supervisor and person in charge of activities, it is necessary to add water gates to rice fields and plantations in rural areas. In addition, it is also essential to plant a Vetiver System to prevent erosion around the road with the help of the community, some of whom have an understanding of the management of road facilities and infrastructure but are still not optimal.